2014
DOI: 10.1007/s11886-014-0544-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Left Ventricular Support Devices During Acute Coronary Syndrome and Percutaneous Coronary Intervention

Abstract: In an effort to improve outcomes in percutaneous coronary intervention (PCI), percutaneous ventricular assist devices (PVADs) have been investigated in (1) high-risk PCI, (2) acute myocardial infarction (AMI) complicated by cardiogenic shock (CS) and (3) in AMI without CS. PCI has become an increasing complex due to an ageing population with complex disease and the frequent presence of impaired LV function. Patients undergoing high-risk PCI in these circumstances are prone to acute cardiovascular collapse. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Mortality and complications were low, and despite the highly complex and mostly extensive coronary artery disease of these patients PCI was successful in all cases. PCI under ECMO in unstable patients with STelevation myocardial infarction and/or cardiogenic shock has been reported to be relatively safe with a good outcome [9,13]. Literature about high-risk PCI under ECMO support in stable patients, however, is scarce to date.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mortality and complications were low, and despite the highly complex and mostly extensive coronary artery disease of these patients PCI was successful in all cases. PCI under ECMO in unstable patients with STelevation myocardial infarction and/or cardiogenic shock has been reported to be relatively safe with a good outcome [9,13]. Literature about high-risk PCI under ECMO support in stable patients, however, is scarce to date.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, high-risk PCI could be performed under mechanical circulatory support using the intraaortic balloon pump (IABP), but its use has seen a decline and downgrade in this regard as studies have failed to display a clear benefit of this form of mechanical circulatory support [6][7][8]. Recently, high-risk PCI under mechanical support, especially extracorporeal membrane oxygenation (ECMO) and the Impella device (Abiomed, Aachen, Germany), has been established as a possible alternative for this group of highrisk patients [9][10][11][12]. Initial reports on the use of venoarterial (VA)-ECMO showed promising results in the treatment of cardiogenic shock due to myocardial infarction [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IABP using could alleviate the burden of the left ventricle and improve cardiac function through reducing left ventricular ejection resistance. Studies have shown that IABP enhanced the pulsation of coronary arteries and provided pulsed blood flow, which were beneficial to reduce the occurrence of acute occlusion and no reflow after PCI treatment 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Different new devices have been proposed as adjunctive treatment in order to sustain cardiac output until the recovery of ventricular function following revascularisation or as a bridge to surgical bypass [20].…”
Section: Use Of New Devices For Mechanical Circulatory Supportmentioning
confidence: 99%